Visualisasi Dakwah Digital melalui Komik Pelangi di Atas Sajadah sebagai untuk Generasi Muda Kalimantan Barat - Eka Rini Widya Astuti; Amidatus Sholihat Jamil; Kharisma Nanda Zenmira; Senjaya Machfudi Zulkif; Tashya (SULUH: Jurnal Seni Desain Budaya, 2026)
The development of digital media has influenced the way young people receive information, including Islamic preaching content. Conventional preaching media are considered less appealing because they tend to be monotonous and less relevant to the characteristics of adolescents in the digital era. This study aims to design the digital comic Pelangi di Atas Sajadah as a digital preaching medium for young people in West Kalimantan. The study employed a Research and Development method with qualitative and quantitative approaches. Data were collected through online observation, interviews, documentation, and questionnaires. Product testing involved 103 respondents aged 12–25 years. The results showed that the digital comic obtained a media expert validation score of 93.33%, a material expert validation score of 85.5%, and a product trial result of 89.5%, all categorized as very good. Therefore, the digital comic Pelangi di Atas Sajadah is considered feasible as a digital preaching medium for young people and was published through Webtoon and Instagram platforms.